Population dynamics of Telenomus fariai (Hymenoptera: Scelionidae), a parasite of Chagas' disease vectors. V. Parasite size and vital space - Rabinovich, Jorge E. (1971)
Some ecological aspects of the developmental process of the endophagous egg parasite Telenomus fariai when reared in Triatoma phyllosoma pallidiPennis eggs, have been investigated. It was shown that mortality among pupae and last instar larvae does not account for the constancy in parasite progeny emergence per host egg, suggesting that if there is any population regulation mechanism based on larval competition, it would be operating among the youngest instars. Simple and multiple linear correlations between parasite size and host egg volume, and progeny production per host egg show that both factors are relevant in determing parasite size, but the effect of progeny production per host egg is on the average three times as important as host egg volume. Vital space (mm3 of host egg volume available per parasite) shows an extremely high correlation (0.970) with parasite size. The elasticity function of vital space on parasite size shows that with increasing values of the former, there is always a higher percentile increase of the latter.